Diagnóstico ecotoxicológico dos efluentes lançados no complexo estuarino do Jundiaí/Potengi, Natal/RN - Nicodemo, Sinara Cybelle Turíbio e Silva (2010)
Untreated effluents that reach surface water affect the aquatic life and humans. This study aimed to evaluate the wastewater s toxicity (municipal, industrial and shrimp pond effluents) released in the Estuarine Complex of Jundiaí- Potengi, Natal/RN, through chronic quantitative e qualitative toxicity tests using the test organism Mysidopsis Juniae, CRUSTACEA, MYSIDACEA (Silva, 1979). For this, a new methodology for viewing chronic effects on organisms of M. juniae was used (only renewal), based on another existing methodology to another testorganism very similar to M. Juniae, the M. Bahia (daily renewal).Toxicity tests 7 days duration were used for detecting effects on the survival and fecundity in M. juniae. Lethal Concentration 50% (LC50%) was determined by the Trimmed Spearman-Karber; Inhibition Concentration 50% (IC50%) in fecundity was determined by Linear Interpolation. ANOVA (One Way) tests (p = 0.05) were used to determinate the No Observed Effect Concentration (NOEC) and Low Observed Effect Concentration (LOEC). Effluents flows were measured and the toxic load of the effluents was estimated. Multivariate analysis - Principal Component Analysis (PCA) and Correspondence Analysis (CA) - identified the physic-chemical parameters better explain the patterns of toxicity found in survival and fecundity of M. juniae. We verified the feasibility of applying the only renewal system in chronic tests with M. Juniae. Most efluentes proved toxic on the survival and fecundity of M. Juniae, except for some shrimp pond effluents. The most toxic effluent was ETE Lagoa Aerada (LC50, 6.24%; IC50, 4.82%), ETE Quintas (LC50, 5.85%), Giselda Trigueiro Hospital (LC50, 2.05%), CLAN (LC50, 2.14%) and COTEMINAS (LC50, IC50 and 38.51%, 6.94%). The greatest toxic load was originated from ETE inefficient high flow effluents, textile effluents and CLAN. The organic load was related to the toxic effects of wastewater and hospital effluents in survival of M. Juniae, as well as heavy metals, total residual chlorine and phenols. In industrial effluents was found relationship between toxicity and organic load, phenols, oils and greases and benzene. The effects on fertility were related, in turn, with chlorine and heavy metals. Toxicity tests using other organisms of different trophic levels, as well as analysis of sediment toxicity are recommended to confirm the patterns found with M. Juniae. However, the results indicate the necessity for implementation and improvement of sewage treatment systems affluent to the Potengi s estuary